Condensation heat and mass transfer of steam with non-condensable gases outside a horizontal tube under free convection. (August 2019) - Lu, Junhui; Cao, Haishan; Li, JunMing
Highlights: Condensation of steam noncondensables (CO2, He, N2 ) on a horizontal tube with free convection is studied. Noncondensables (CO2, He, N2 ) molar fraction ranges from 0.05 to 0.2. Effects of noncondensable gas concentration, surface subcooling and composition are analyzed. A model is developed to predict the condensation heat transfer coefficient of steam with a noncondensable gas. A condensation heat transfer correlation is proposed. Abstract: The condensation heat and mass transfer of steam-He, steam-N2 and steam-CO2 mixtures on a horizontal tube under free convection was studied experimentally and theoretically. A model was developed to predict the total condensation heat transfer coefficient of these mixtures and the model considered the effects of suction, fog formation and the variation of the mixture density and molecular weight across the diffusion layer. The experiments were conducted to investigate the effects of noncondensable gas component, concentration and surface subcooling. The condensation heat transfer coefficients are significantly reduced due to the presence of noncondensable gases. The condensation heat transfer coefficient decreases slowly as the surface subcooling increases and the subcooling effect decreases with increasing noncondensable gas concentration. For a given noncondensable gas mole fraction and a given surface subcooling, the steam-He mixture has the highest measured condensation heat transfer coefficient, followed by the steam-N2 mixture and the steam-CO2 mixture has the lowest measured condensation heat transfer coefficient. But for a given noncondensable gas mass fraction and a given surface subcooling, the measured condensation heat transfer coefficient of the steam-He mixture is the lowest, followed by the steam-N2 mixture, CO2 mixture. The model predicts the relative errors of the total condensation heat transfer coefficients of these mixtures within ±30%. A condensation heat transfer correlation was developed based on the experimental data and the correlation achieved an uncertainty of less than 20%.